Sources of Nepali Army’s military effectiveness during the Anglo-Nepal War - Subba, Phanindra (Unity Journal, 2020)
Military effectiveness is the process by which the military converts available material and political resources into military power. The organizational revolution that took place in Europe during the period, 1500- 1700, multiplied the military effectiveness of the European states. This paper, however, aims to assess the military effectiveness of the Nepalese Army during the Anglo- Nepal War, 1814-16, in the context of the failure of many of the armies of South Asia to mount an effective resistance against the colonial onslaught. Further, it explores the sources of the Nepali Army’s effectiveness in performance rooted in Prithvi Narayan Shah’s national army in its formative phase. His concept of the nation-state, the creation of a permanent army and his policy of not limiting recruitment and promotions to the natives of Gorkha laid the foundation for a loyal, competent multi–ethnic army. Moreover, this paper states that the institutional stability provided by his successors during a period of political turbulence spared the army time to consolidate and pass its institutional memory to the following generation. War is a brutal business, and the military effectiveness of armies is tested in the battlefield in which weaknesses are severely punished after their exposures. Strong states fight to win, the weak to survive. The paper concludes that the Nepali Army proved its military effectiveness during the Anglo-Nepal War by ensuring Nepal’s continued survival as an independent, sovereign state ever.